MICROELEMENTS AND MICROELEMENTOSIS AND THEIR SIGNIFICANCE IN CHILDHOOD - S.V. Bel'mer; T.V. Gasilina ("Paediatrician" Publishers LLC, 2008)
A physiological role of microelements (zinc, selenium, iodine, chrome, molybdenum, silicon, vanadium) and its participation as co-factors of key enzymes in normal vital functions in human was examined. A significance of microelements in formation and functioning of immune system, bowels and antioxidant defense in children was analyzed. A consequence of deficiency of microelements was described. While children of first year of life are most vulnerable for a deficiency of microelements, it's necessary to consider in development of nutrition of this age group. Key words: microelements, deficiency, nutrition.